Purple corn as industrial raw material - Lavado Soto, Mooner Aurelio (2013)
Currently, the purple corn is used in integral form, ie without separating grains cob, which is an unreasonable use, because it is discarded grains, which are highly nutritious foods. Motivated by this background, this study aims purple corn processing, products for industrial use. These purple corn processed products are: cob grits, flour and bran. The crushed cob is used to obtain an aqueous solution, commonly called “chicha morada, which is also used to prepare purple porridge”. The flour can be used in baking, and bran for animal feed.